Unfulfilled Promises, Future Possibilities: The Refugee Resettlement System in the United States. (June 2014) - Brown, Anastasia; Scribner, Todd
World War II caused the displacement of millions of people throughout Europe. In response, the United States initiated a public-private partnership that assisted in the resettlement of hundreds of thousands of the region's displaced persons. For nearly 40 years after the War, the US commitment to refugee resettlement played out in an ad hoc fashion as it responded to emerging crises in different ways. During this period the government's involvement with resettlement became gradually intertwined with that of nongovernmental resettlement agencies, which came to play an increasingly vital role in the resettlement process. The budding relationship that began in the middle decades of the twentieth century set the foundation for an expansive and dynamic public-private partnership that continues to this day. The Refugee Act of 1980 solidified the relationship between resettlement agencies and the federal government, established political asylum in US law, and created the refugee resettlement program and a series of assistance programs to help refugees transition to life in the United States. This legislation marked a decisive turning point in the field of refugee resettlement. Since passage of the Act, the United States has resettled more than two million refugees, providing them with the opportunity to start a new life. Nevertheless, almost as soon as it was established, federal backing for the domestic resettlement program began to erode, placing the program under increasing stress. Financial and programmatic support was quickly reduced because of budgetary pressures and a changing political climate in Washington, DC. Administrative control of the program was assigned to federal agencies that are responsible for different facets of the process. However, coordination and information sharing between these agencies and with resettlement agencies has been less than optimal. The lack of adequate support for the resettlement program has placed substantial strain on refugee receiving communities and on resettlement agencies. Receiving communities have experienced particular strain as a result of secondary migration and a lack of resources to assist in refugee integration. In light of these issues, this paper highlights specific improvements that could be made to the domestic resettlement program that would ensure that the United States will remain in a strong position to welcome refugees for years to come.